ROS robotics projects build and control robots powered by the robot operating system, machine learning, and virtual reality - Gandhinathan, Ramkumar (Packt Publishing Ltd., 2019)
ROS is one of the most widely-used robotics middleware by several industries for building robot-specific applications. This book is an upgrade to the previous edition and introduces you to the latest ROS approaches, basic concepts of ROS-2 and newer ROS packages, with interesting projects and new features added to the previous projects.
Keywords: Robots -- Programming; Robotics -- Popular works; Robots; Programmation; Robotique; Ouvrages de vulgarisation; Robotics; Robots; Programming; Popular works